Harwell's new business centre - Guy, Ian
This article describes the newly launched Harwell International Business Centre for Science & Technology and describes the history of the site, its occupant firms, and the centre's plans for future expansion.
The writer reports how Harwell, which provided the scientific base for the UK's nuclear development programme, is now becoming an international centre of scientific, technological and business excellence. Harwell's history and plans for future expansion are discussed.